Efficacy of low‐molecular‐weight heparin on the outcomes of in vitro fertilization/intracytoplasmic sperm injection pregnancy in non‐thrombophilic women: a meta‐analysis. (5th June 2018) - Yang, Xiu‐Li; Chen, Fei; Yang, Xiu‐Ying; Du, Guan‐Hua; Xu, Yang
Abstract: Introduction: The aim of our study was to evaluate the effect of low‐molecular‐weight heparin on pregnancy outcomes in women without thrombophilia during in vitro fertilization/intracytoplasmic sperm injection treatment. Material and methods: We searched Pubmed, Web of Science, Embase, Cochrane and CNKI (from inception to 2 February 2018). Our study identified randomized controlled trials or quasi‐randomized controlled trials comparing low‐molecular‐weight heparin subcutaneous treatment with no treatment or only luteal support control. The outcomes included live birth rate, clinical pregnancy rate and miscarriage rate. Results: Five trials, including 935 women receiving in vitro fertilization/intracytoplasmic sperm injection treatment, were included in meta‐analyses. There were 458 women receiving low‐molecular‐weight heparin and 477 in the control group. No significant differences for live birth rate, clinical pregnancy rate and miscarriage rate were found between the low‐molecular‐weight heparin and control groups. Of them, four trials reported live birth rate as an outcome and the risk ratio was 1.13 (95% confidence interval 0.88–1.43, p = 0.34). All five trials reported clinical pregnancy rate as an outcome, the risk ratio was 1.08 (95% confidence interval 0.87–1.32, p = 0.47). Three trials reported miscarriage rate and the risk ratio was 0.58 (95% confidence interval 0.30–1.10, p = 0.09). In women with two or more failed in vitro fertilization/intracytoplasmic sperm injection cycles, the risk ratio of live birth rate was 1.15 and the risk ratio of clinical pregnancy rate was 1.17. In women with three or more failed in vitro fertilization/intracytoplasmic sperm injection cycles, the risk ratios of live birth rate and clinical pregnancy rate were 1.36 and 1.35, respectively. Conclusions: Our results suggested that low‐molecular‐weight heparin had no effect on pregnancy success rate in non‐thrombophilic women undergoing in vitro fertilization/intracytoplasmic sperm injection treatment. However, to justify the use of low‐molecular‐weight heparin in clinical practice, multicenter trials are still necessary.